Iowa's geological past : three billion years of earth history - Anderson, Wayne I., 1935- (Bur oak original., 1998)
Iowa's rock record is the product of more than three billion years of geological processes. The state endured multiple episodes of continental glaciation during the Pleistocene Ice Age, and the last glacier retreated from Iowa a mere (geologically speaking) twelve thousand years ago. Prior to that, dozens of seas came and went, leaving behind limestone beds with rich fossil records. Lush coal swamps, salty lagoons, briny basins, enormous alluvial plains, ancient rifts, and rugged Precambrian mountain belts all left their mark. In Iowa's Geological Past, Wayne Anderson gives us an up-to.